Informal cross-border trade in Africa - Pace, Kathryn; Bouët, Antoine; Glauber, Joseph W. (International Food Policy Research Institute, 2019)
As ICBT appears to be so large and is heavily linked to food security, economic development, and women’s empowerment, it is important to obtain accurate measurements of this type of trade. More accurate data can improve the statistical measurements of balance of payments and external accounts, improving global trade measurement and modeling, and facilitate the development of more accurate domestic food balance sheets. Overall, measurement of ICBT in Africa can provide a more accurate picture of other aspects related to informal trade, including information on informal labor markets and movement patterns of staple foods during periods of crises. Each of these provides the opportunity for better policymaking using reliable and accurate data.